2017
DOI: 10.3390/ijms18102074
|View full text |Cite
|
Sign up to set email alerts
|

Fascaplysin Exerts Anti-Cancer Effects through the Downregulation of Survivin and HIF-1α and Inhibition of VEGFR2 and TRKA

Abstract: Fascaplysin has been reported to exert anti-cancer effects by inhibiting cyclin-dependent kinase 4 (CDK4); however, the precise mode of action by which fascaplysin suppresses tumor growth is not clear. Here, we found that fascaplysin has stronger anti-cancer effects than other CDK4 inhibitors, including PD0332991 and LY2835219, on lung cancer cells that are wild-type or null for retinoblastoma (RB), indicating that unknown target molecules might be involved in the inhibition of tumor growth by fascaplysin. Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Quantitative real-time PCR was performed as previously described [ 46 ]. Briefly, 2 μg of total RNA extracted from cultured cells by using TRIzol (Invitrogen, Waltham, MA, USA) and cDNA synthesis was performed by using a high-capacity cDNA reverse transcription kit (Applied Biosystems, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative real-time PCR was performed as previously described [ 46 ]. Briefly, 2 μg of total RNA extracted from cultured cells by using TRIzol (Invitrogen, Waltham, MA, USA) and cDNA synthesis was performed by using a high-capacity cDNA reverse transcription kit (Applied Biosystems, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…As previously described [ 46 ], BALB/c-nude mice were used as human tumor xenograft models. HepG2 or SK-HEP-1 cells (1 × 10 6 ) were harvested and suspended in 100 µL of FBS-free medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of the antitumor effect of fascaplysin demonstrated on several carcinoma models indicate that fascaplysin is close to some drug groups such as intercalating agents, inhibitors of serine-threonine, and tyrosine kinases. Additionally, fascaplysin increases phosphorylation of AKT/PKB and adenosine monophosphate-activated protein kinase (AMPK), which feature anti-apoptotic or pro-survival functions in cancer [ 41 ]. In detail, fascaplysin abolishes the phosphorylation of mTOR, 4EBP1, and p70S6K1, which trigger the cap-dependent translation machinery and affect the expression of oncoproteins, such as survivin, c-myc, cyclin D1, VEGF, and HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that fascaplysin exerts anti-cancer effects through the down-regulation of survivin and hypoxia inducible factor-1ɑ (HIF-1ɑ) by suppressing mechanistic target of rapamycin (mTOR)-eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1)-mediated 5′-cap-dependent translation [ 5 ]. In addition, fascaplysin exerts anti-angiogenic effects by suppressing vascular endothelial growth factor receptor 2 (VEGFR2) through non-competitive inhibition of Asp-Phe-Gly (DFG)-out [ 6 ]. However, ways to improve the anti-cancer efficacy of fascaplysin for clinical application are poorly understood.…”
Section: Introductionmentioning
confidence: 99%